Steady State and Dynamic Interaction Analysis in Multivarible Control System - Renanto Handogo; Gede Wibawa; Moch. Arief Hidayat; PT IKPT Jakarta (ASEAN Journal of Chemical Engineering, 2004)
Relative gain array (RGA) and average dynamic gain array (ADGA) have been investigated as a measure for interaction of multi-input multi-output (MIMO) 2x2 system. Several examples have been chosen to represent MIMO with various time constants and dead time of first order plus dead time. The ratio of off-diagonal and on-diagonal element time constants of the transfer function processes (6) has shown more dominance to interaction than ratio of off-diagonal and on-diagonal element dead times of the transfer function processes (0,) . RGA, INA,and ADGAgive the same result for t'j 3 1 and INA and ADGA should be used for t'j 1 regardless the value of do